Lingering Shadows and New Horizons: The Complex Legacy of the COVID-19 Lockdown in Greece - Christos Tsimirikas; Panagiota Tragantzopoulou (COVID, 2025)
The COVID-19 pandemic caused unprecedented global disruptions, profoundly impacting mental health and social well-being. While significant research has addressed the negative health consequences of social isolation, little is known about the post-pandemic experience, particularly in Greece. This qualitative study investigates the lasting effects of social isolation during the COVID-19 lockdowns on individuals in Greece, exploring both the negative and positive consequences in the post-pandemic context. One-on-one interviews were conducted with fifteen participants, and the data were analyzed using a thematic analysis. The findings revealed that the lockdown had a profound and enduring impact. Many participants reported heightened social anxiety, a sense of disconnection, and lingering fear about re-engaging in normal social interactions. Nostalgia for pre-pandemic life, characterized by greater social connection and freedom, was a recurring theme. Despite these challenges, the study also highlighted positive outcomes. Some participants viewed enforced solitude as an opportunity for self-reflection and growth, discovering new interests or deepening their understanding of personal values and goals. These findings underscore the complex and enduring effects of social isolation. The study calls for targeted interventions to foster social connectedness and mental health resources, ensuring support as society transitions to a post-pandemic reality. Continued attention from policymakers and public health professionals is crucial.